Reaproveitamento de pneumáticos inservíveis na construção de um sistema individual de tratamento de esgoto doméstico: contribuição para a aplicação da logística reversa no município de Tucuruí-PA - FREITAS, Pablo Virgolino (2022)
It was proposed study of the economic viability of implementing an alternative individual treatment system of domestic sewage with two tanks arranged in series preceding an anaerobic filter with fixed bed with upflow, whose raw material used for the construction of the containment structure of these effluents are unserviceable tires fitted together with asphaltic mass, in order to achieve a watertight set that meets the recommendations of the NBR 7229/1993 (Project, construction and operation of septic tank systems) and the NBR 13969/1997 (Septic tanks - Complementary treatment plants and final disposal of wastewater - Project, construction and operation). The main expectation of the use of tires as raw material in works building is its removing from the environment, thus practicing the provisions of the National Solid Waste Policy and reverse logistics waste, and the proposal of raw materials of low-cost and easy to purchase. Therefore, the system was deployed in a residence in the most populous neighborhood of the city of Tucuruí, and which hadn’t individual treatment of sewage system with minimal technical criteria. Compared up the budgets for the construction of alternative and conventional too, made with masonry and ceramic blocks, systems, prevailing the economic viability of the system structured on tires with 9.9% savings. A projection of the tires quantitative removed from the environment was made in the case of this technology would be accepted by 100% of neighborhood homes, resulting in a total of 55903 tires.